Descriptions of the mature larvae for two species of Pseudopyrochroa from Taiwan (Coleoptera: Pyrochroidae: Pyrochroinae), with notes on their natural history - Young, Daniel K.; Hsiao, Yun; Liang, Wei-Ren; Lee, Chi-Feng (Zootaxa, 2016)
Field collections and rearing have established the first species-level associations for larvae of Pyrochroidae from Taiwan. Larvae of Pseudopyrochroa carinifrons and Pseudopyrochroa fainanensis were collected from beneath bark and in coarse, decaying woody debris of dead logs and successfully reared to the respective adult stages. The mature larvae are described and salient features are illustrated. Notes on larval habitats and natural history are also provided.